Disrupting the Biodiversity–Ecosystem Function Relationship: Response of Shredders and Leaf Breakdown to Urbanization in Andean Streams - Zúñiga-Sarango, Wilson; Gaona, Fernando P.; Reyes-Castillo, Valeria; Iñiguez-Armijos, Carlos (Frontiers in Ecology and Evolution, 2020)
Urbanization is a major driver of stream ecosystems impairment and often associated with multiple stressors and species loss. A challenge is to understand how those stressors alter the relationship between biodiversity and ecosystem functioning (B-EF). In Andean streams of southern Ecuador, we assessed the response of shredder diversity and organic matter breakdown (OMB) to urbanization and identified the urban-associated stressors disrupting the B-EF relationship. A leaf-litter bag experiment during stable flow conditions in 2016 was carried out to quantify total OMB and shredder-mediated OMB, which was estimated to represent the B-EF relationship. We calculated the taxonomic and functional diversity of shredder invertebrates associated with leaf packs. Also, a suite of physicochemical and habitat stressors was weekly measured during the field experiment. Along with the urbanization gradient, both taxonomic and functional diversity of shredders declined while OMB rates decayed. Shredders were absent and their contribution to OMB was null at the most urbanized sites. The B-EF relationship was interrupted through nutrient enrichment and physical habitat homogenization as a consequence of urbanization. These results demonstrate how species loss propagates to ecosystem functions in urbanized streams and how environmental stressors alter the B-EF relationship. Better land-use practices are crucial in Andean catchments to guarantee ecosystem services which are the result of successful B-EF relationships.